2019
DOI: 10.1155/2019/3813298
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Progress towards Achieving “VISION 2020: The Right to Sight” Initiative in Ghana

Abstract: Purpose. The aim of this study was to analyse eye health delivery in Ghana and examine the progress towards achieving VISION 2020 indicator targets. Methods. This descriptive cross-sectional study was conducted between October 2017 and May 2018. It used a mixed method approach including desk-based reviews, a questionnaire-based survey of eye facilities in Ghana, and interviews with eye health system stakeholders to collect information on eye health delivery in facilities owned by the Ghana Health Service (GHS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Notably, a systematic review and meta-analysis by Hashemi et al [ 30 ] provided evidence that the prevalence of myopia, hyperopia, and astigmatism among adults in Africa was 11.4%, 38.6%, and 16.2%, respectively, as opposed to 14.2%, 3.0%, and 6.2%, respectively in children. The central role of optometrists in the provision of quality refractive error services in Ghana is inevitably needed in reducing the burden of avoidable visual impairment and blindness in the country [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a systematic review and meta-analysis by Hashemi et al [ 30 ] provided evidence that the prevalence of myopia, hyperopia, and astigmatism among adults in Africa was 11.4%, 38.6%, and 16.2%, respectively, as opposed to 14.2%, 3.0%, and 6.2%, respectively in children. The central role of optometrists in the provision of quality refractive error services in Ghana is inevitably needed in reducing the burden of avoidable visual impairment and blindness in the country [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 There are only four ophthalmologists and 13 optometrists 15 serving the northern parts of the country with a population of 5.1 million whereas in the south there are 88 ophthalmologists and 357 registered optometrists serving approximately 23 million people. 15,16 This suggests that the ophthalmologist-and optometrist-to-population ratio in the north is 1:1,100,000 and 1:392,000 respectively. 15 These proportions are three times higher than the national proportion of 1:311,080 for ophthalmologist/population and five times higher (1:76,508) for optometrist/population.…”
mentioning
confidence: 99%
“…15,16 This suggests that the ophthalmologist-and optometrist-to-population ratio in the north is 1:1,100,000 and 1:392,000 respectively. 15 These proportions are three times higher than the national proportion of 1:311,080 for ophthalmologist/population and five times higher (1:76,508) for optometrist/population. Paediatric eye clinics and paediatric ophthalmologists are non-existent in the north.…”
mentioning
confidence: 99%
“…The World Health Organization (WHO) recommendation for human resource distribution for low-income countries, highlights that a minimum of four Ophthalmologists should serve a million population [ 26 ]. In Ghana, there are 91 ophthalmologists serving a population of approximately 30 million [ 28 ]. This number is less than what is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the report showed a limited number of sub-specialty (including experts in DR treatment) with the exception of paediatric ophthalmology [ 29 ]. Furthermore, a study analysing eye health delivery in Ghana by Morny and colleagues showed a positive skewness in the distribution of human resources across two regions (Ashanti and Greater Accra regions) and with limited specialist eye care (such as DR services) equipment across the nation [ 28 ]. Our findings show an under-utilisation of human resources, especially with regions like the Eastern, Central, Western, Upper East and Upper West having no access to any form of DR treatment services.…”
Section: Discussionmentioning
confidence: 99%